Analysis of a Tray Dryer Machine Using a Microcontroller-Based Data Acquisition System using LabVIEW - Budhy Setiawan; Erlillah Rizqi Kusuma Pradani; Donny Radianto; Abid Nabawi (Universitas Islam Raden Rahmat, Malang, 2025)
Drying equipment is used for large needs of optimal temperature, humidity, the time required until the material is dry and the maturity is right. The tray dryer is equipped with a monitoring and data acquisition system that can display accurate temperature, humidity, weight and air flow data using a microcontroller and LabVIEW. Data from the sensor will be received by the microcontroller. LabVIEW will process and display data in the form of graphs on the monitor screen and data will be recorded every time in Excel. The error value on the reading of temperature and humidity sensors is 0 - 0.24%. The error value on the weight sensor is 0.45%. 1437.47 Joules is the average amount of energy absorbed by the substrate during the drying process. Sampling data retrieval in this data logger data is 100 ms and produces 165,465 data. The results of the display of parameter data including temperature, humidity, and weight per process in LabVIEW are displayed in graphs for each parameter with a GUI interface between the user and the machine.